UPAYA GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS II PADA TEMA 2 MELALUI MEDIA ORIGAMI DI SD MUHAMMADIYAH INDONESIANA TIDORE - Julita Idrus; Devi Wahyu Ertanti; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
In the learning process in the classroom students often come in and out of class, chat with their peers, are passive when learning, even in terms of answering, questions, they have low abilities and there are students wholl diffcult to write, read and do assignments given by the teacher. This research is a learning approach that connects various subjects that reflect the real world around them and within the ran e of abilities, student development and increase student interest in learning. The objectives mentioned above are carried out with this type of qualitative research, in this study the authors use two data sources, namely data sources, primary and secondary data. Interviews aimed directly at homeroom teachers of class II, principals and teachers at SD Muhammadiyah Indonesiana Tidore using interview guidelines with the aim of obtaining data about teacher efforts, constraints, solutions in increasing student interest in grade Il on theme 2 playing in my environment through origami media. Increase student interest in learning through an interesting medium, namely origami media that can attract visual eyes and fine motor skills and can increase students 'interest and right brain intelligence, aims to broaden students' insight and be creative in their own creations with guidance by teachers in learning interest can make students able follow the learning process well.